Islamic Macroeconomics-A New Paradigm - Agus, Agus; Abdul Majid, M. Shabri (Publisher Cv. Inara, 2022)
This research discusses a new paradigm in Islamic macroeconomics, where conventional macroeconomic instruments, namely interest, have not been able to carry out or reduce the number of national crises that often occur in Indonesia. This research is a descriptive qualitative research with a Literature review approach. The results of the research obtained, that Islamic macroeconomics have instruments that can flatten the economy, where the instrument in question is the instrument of the profit sharing system. In the profit-sharing system, there is no imbalance on the road, everything must be transparent and must work together, so that the results obtained are maximum. Likewise with losses, if losses are presented, it is not only borne by one party, but both parties must also bear. This is the so-called equality in the economy which is a new paradigm in the Macro-Islamic system.